An Attitudinal Analysis of Student-Teacher Talk on Online Classroom Interaction - Nur Aenida, Nadia Alifa; Herdiawan, Rama Dwika; Rofi'i, Agus (Allure Journal, 2022)
This study is conducted to find out the attitudinal resources used by a student-teacher talk on online classroom interaction through appraisal framework (Martin White, 2005). This research used a qualitative approach with adopted critical discourse analysis (CDA) research design. The subjects of this research were students in the fifth semester and teachers in Universitas Majalengka. The findings show that the dominant type of attitudinal system of student and teacher talk on online classroom interaction; The dominant attitude device found by students is Judgment which constitutes 23,33%, followed by Appreciation (16,67%), and Affect (13,33%). The dominant attitude device found by the teacher is Affect which constitutes 31,14%, followed by Appreciation (21,31%), and Judgement (11,47%). Students can use this kind of analysis a develop speaking skills based on character education that can provide basic rules for life and practice behaviors that reflect values. The way teachers and students express their emotional reactions shows their aspects and their relationships through the choice of language. The contribution of student and teacher talk in terms of appraisal analysis are; a sense of curiosity, sense of communicative, sense of responsibility, sense of respect for achievement, sense of honesty, and sense of independent.